EXPLORING FARMERS’ PERCEPTIONS OF CLIMATE SMART AGRICULTURE: EVIDENCE FROM NORTHERN NIGERIA - Terdoo, Fanen (FUDMA Journal of Sciences, 2020)
The aim of climate-smart agriculture (CSA) is to help farmers increase productivity, adapt their methods, become resilient to climate impacts and reduce their greenhouse gas emissions. However, there has been little published research on the perceptions and knowledge of farmers as to how this approach can fulfill its potential, especially in Africa. This paper presents a study based on interviews and group discussions conducted among farmers in some rural communities in Northern Nigeria. It reveals that the strength of CSA lies in its ability to integrate agricultural productivity with environmental targets and address the livelihood needs and cultural biases of local farmers. It also identified differences in the perception of different groups within society. For example, the younger farmers who possess little farmland showed optimism in the potential of the CSA approach to address livelihood and environmental challenges while the older farmers with larger farmlands were generally uncertain and suspicious. The analysis of interviews presented could be used to identify target groups on which to focus CSA, assuming that groups with a significantly greater proportion of farmlands could have more impact on the environment. The study suggests a continuous effort is made to develop knowledge and build capacity of local farmers and experts. Lessons from this study are important in developing the knowledge and capacities that will make CSA a reality. Further studies across Africa which take local specificities and priorities into consideration are needed.
Keywords: Knowledge, attitudes, agricultural innovations, rural farmers, Katsina State.